TDS dan pH yang Dihasilkan Penjernih Air Sarang Tawon Akibat Perbedaan Ketebalan dan Kerapatan Media Filter Sabut Kelapa - Astuti, Dinda Kusuma Widi; Jaya, Allan Restu; Nindito, Dwi Anung (Jurnal Teknik Sipil, 2025)
Sarang Tawon water purifier uses filtration principle which is done repeatedly through certain filter media that are arranged in layers. The water quality as the filtration result is influenced by the filtration system and the type of filter media used and the duration of purifying process. The factor of thickness and filter media density were neglected until causing problem in the duration of water purifying process. This research aimed to find out the influence of thickness difference and filter media density of Sarang Tawon water purifier towards the parameter of Total Dissolved Solids (TDS) and pH. The experimental method was applied by testing the thickness of zeolite stone filter media combination, ginger coral, and coconut fiber from the Sarang Tawon water purifier with radius 4R/3, R, and 2R/3 where R=3 inches. The density variations of coconut fiber filter media were 20%, 40%, 60%, 80% and 100%. The research results showed that the thickness of filter media in Sarang Tawon water purifier tool with radius 4R/3 with coconut fiber filter media density was 80% owning the ability to increase the highest pH value. There was increase of TDS parameter in each trial caused by the dissolved of ginger coral filter media, but it did not show significant number. TDS parameter resulted by the tool with radius 2R/3 with density variation of coconut fiber filter media amounted 80% showed a relatively stable value.